BYD Ameliorates Oxidative Stress-Induced Myocardial Apoptosis in Heart Failure Post-Acute Myocardial Infarction via the P38 MAPK-CRYAB Signaling Pathway - Zhang, Yi; Li, Chun; Meng, Hui; Guo, Dongqing; Zhang, Qian; Lu, Wenji; Wang, Qixin; Wang, Yong; Tu, Pengfei (Frontiers in Physiology, 2018)
Aims: Heart failure (HF) post-acute myocardial infarction (AMI) contributes to increasing mortality and morbidity worldwide. Baoyuan decoction (BYD) is a well-known traditional Chinese medicine formula that exhibits myocardial protection clinically. The aim of this study was to identify the effects of BYD on oxidative stress-induced apoptosis in HF post-AMI and characterize the underlying mechanism. Methods and Results: In our study, we constructed left anterior descending (LAD)-induced AMI rat models and a macrophage-conditioned media (CM)-induced H9C2 injury model. In vivo, BYD could protect cardiac functions, decrease inflammatory cell infiltration and inhibit oxidative stress-induced apoptosis. In vitro, BYD inhibited cellular apoptosis and regulated the expressions of key apoptotic molecules, including reducing the expression of B cell lymphoma-2 (Bcl-2) associated X protein (Bax) and cleaved caspase-3 and -9. Interestingly, the P38 mitogen-activated protein kinase (MAPK)-αB-crystallin (CRYAB) signalling pathway was activated by BYD treatment, and the P38 MAPK inhibitor SB203580 could reverse the protective effects of BYD. Conclusions: This study identified that BYD protected against oxidative stress-induced myocardial apoptosis via the P38 MAPK-CRYAB pathway. CRYAB may become a novel therapeutic target for acute myocardial infarction.